Unveiling the Cytological Enigma of Malignant Spindle Cell Neoplasm of Peripheral Nerve Sheath: A Clinicopathological Image - Shreya Giri Goswami; Poornima Pandey; Jayashree Bhawani (Journal of Clinical and Diagnostic Research)
Peripheral Nerve Sheath (PNS) tumours are rare neoplasms arising from deeper soft tissues, peripheral nerves, perineural cells, or Schwann cells with ectomesenchymal origins [1]. The incidence rate is between 4-13%, with the upper extremity being the most commonly involved site (45%) [2]. The role of Fine Needle Aspiration Cytology (FNAC), based on the cytomorphology of these neoplasms of the PNS, is challenging and often confusing, underscoring the complex diagnostic nature of the lesions. Therefore, FNAC details were highlighted by presenting a clinicopathological image and providing insight into the intricate cytomorphology involved.